2017
DOI: 10.1371/journal.pone.0178316
|View full text |Cite
|
Sign up to set email alerts
|

Gene signature associated with benign neurofibroma transformation to malignant peripheral nerve sheath tumors

Abstract: Benign neurofibromas, the main phenotypic manifestations of the rare neurological disorder neurofibromatosis type 1, degenerate to malignant tumors associated to poor prognosis in about 10% of patients. Despite efforts in the field of (epi)genomics, the lack of prognostic biomarkers with which to predict disease evolution frustrates the adoption of appropriate early therapeutic measures. To identify potential biomarkers of malignant neurofibroma transformation, we integrated four human experimental studies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Our study also validated the importance of previously identified target genes on chromosome arm 17q in MPNST, including BIRC5, TK1, and TOP2A. 22,23,68,82,83 We have previously suggested that high expression levels of these genes and their encoded proteins represent a prognostic risk profile among patients with MPNST. 20 In conclusion, we report an integrative molecular study of MPNSTs at the genomic and transcriptomic levels.…”
Section: Discussionsupporting
confidence: 85%
“…Our study also validated the importance of previously identified target genes on chromosome arm 17q in MPNST, including BIRC5, TK1, and TOP2A. 22,23,68,82,83 We have previously suggested that high expression levels of these genes and their encoded proteins represent a prognostic risk profile among patients with MPNST. 20 In conclusion, we report an integrative molecular study of MPNSTs at the genomic and transcriptomic levels.…”
Section: Discussionsupporting
confidence: 85%
“…Nonetheless, the comparisons of MPNST subtypes and neurofibromas supported a previous meta-analysis showing upregulation of genes related to DNA replication and cell cycle pathways in MPNSTs relative to benign tumours, as well as downregulation of genes relevant for peripheral nervous system development and immune complement activation. 68 Our study further suggested that downregulation of immune activity was specific to the immune deficient subtype, but it is not known whether this is consistent in comparison with atypical neurofibromas. Downregulation of differentiation markers such as SOX10 was found in the least aggressive subtype of MPNSTs relative to neurofibromas, and this has also been shown in a comparison of MPNSTs with normal Schwann cells, supporting appropriateness of the neurofibromas as a non-malignant reference.…”
Section: Discussionmentioning
confidence: 46%
“…Our study also validated the importance of previously identified target genes on chromosome arm 17q in MPNST, including BIRC5, TK1, and TOP2A . 22 , 23 , 68 , 82 , 83 We have previously suggested that high expression levels of these genes and their encoded proteins represent a prognostic risk profile among patients with MPNST. 20 …”
Section: Discussionmentioning
confidence: 99%
“…TOP2A, one of the top 20 genes upregulated in MPNST [41], encodes the enzyme DNA topoisomerase II alpha, which controls and alters the topologic states of DNA during transcription. Matching this observation, PNF1 tumor cell lines displayed drug-resistance to anthracycline topoisomerase inhibitors, e.g., idarubicin, epirubicin, mitoxantrone, and doxorubicin.…”
Section: Top2a and Chek1 Gene Product Inhibitorsmentioning
confidence: 99%